Atomistic modeling of tribological properties of Pd and Al nanoparticles on a graphene surface - Khomenko, Alexei; Zakharov, Miroslav; Boyko, Denis; Persson, Bo N. J. (Beilstein Journal of Nanotechnology, 2018)
Background: The frictional properties of nanoparticles have been studied to gain insight into the fundamental origin of sliding friction.Results: Using molecular dynamics we investigate frictional properties of aluminum and palladium nanoparticles deposited on a graphene layer. We study the time evolution of the total momentum of the system, the total and potential energies, the temperature, the velocity and position of the center of mass, the dimensions of the nanoparticle, and the friction and substrate forces acting on the particle. We also study how the friction force depends on the nanoparticle–graphene contact area and the temperature.Conclusion: The tribological properties of nanoparticles strongly depend on the materials. The particles move in an irregular (saw-like) manner. The averaged friction force depends nearly linearly on the contact area and non-monotonously on temperature. We observe ordered crystalline domains of atoms at the bottom surface of the metal particles, but the peaks of radial distribution function are blurred indicating that the nanoparticles are amorphous or polycrystalline.
Keywords: aluminum; friction force; graphene; nanoparticle; nanotribology; palladium

Springer Handbook of Nanotechnology - Bhushan, B. (Springer, 2004)

Nanotribology and Nanomechanics - Bhushan, B. (Springer, 2005)

(untitled) - Mertens, F.; Göddenhenrich, T.; Dietzel, D.; Schirmeisen, A. (J. Appl. Phys., 2017)

(untitled) - Marx, T.; Shen, X.; Dietzel, D.; Schirmeisen, A. (Langmuir, 2017)

(untitled) - Mazo, J. J.; Dietzel, D.; Schirmeisen, A.; Vilhena, J. G.; Gnecco, E. (Phys. Rev. Lett., 2017)

(untitled) - Feldmann, M.; Dietzel, D.; Tekiel, A.; Topple, J.; Grütter, P.; Schirmeisen, A. (Phys. Rev. Lett., 2016)

(untitled) - Dietzel, D.; Brndiar, J.; Štich, I.; Schirmeisen, A. (ACS Nano, 2017)

(untitled) - Mao, Y.; Zhang, Y. (Appl. Therm. Eng., 2014)

(untitled) - He, A.; Huang, S.; Yun, J.-H.; Wu, H.; Jiang, Z.; Stokes, J.; Jiao, S.; Wang, L.; Huang, H. (Tribol. Lett., 2017)

(untitled) - Khomenko, A. V.; Prodanov, N. V. (J. Phys. Chem. C, 2010)

(untitled) - Khomenko, A. V.; Prodanov, N. V.; Persson, B. N. J. (Condens. Matter Phys., 2013)

The Art of Molecular Dynamics Simulation - Rapaport, D. C. (Cambridge University Press, 2004)

(untitled) - Dietzel, D.; Feldmann, M.; Schwarz, U. D.; Fuchs, H.; Schirmeisen, A. (Phys. Rev. Lett., 2013)

(untitled) - Dietzel, D.; Mönninghoff, T.; Herding, C.; Feldmann, M.; Fuchs, H.; Stegemann, B.; Ritter, C.; Schwarz, U. D.; Schirmeisen, A. (Phys. Rev. B, 2010)

(untitled) - Zhou, X. W.; Wadley, H. N. G.; Johnson, R. A.; Larson, D. J.; Tabat, N.; Cerezo, A.; Petford-Long, A. K.; Smith, G. D. W.; Clifton, P. H.; Martens, R. L.; Kelly, T. F. (Acta Mater., 2001)

(untitled) - Berendsen, H. J. C.; Postma, J. P. M.; van Gunsteren, W. F.; DiNola, A.; Haak, J. R. (J. Chem. Phys., 1984)

2017 IEEE 7th International Conference Nanomaterials: Application Properties (NAP) - Khomenko, A. V.; Boyko, D. V.; Zakharov, M. V.; Khomenko, K. P.; Khyzhnya, Y. V. (Molecular dynamics of aluminum nanoparticles friction on graphene)

(untitled) - Khomenko, A. V.; Prodanov, N. V. (Carbon, 2010)

(untitled) - Prodanov, N. V.; Khomenko, A. V. (Surf. Sci., 2010)

(untitled) - Persson, B. N. J. (Phys. Rev. B, 1995)

(untitled) - Persson, B. N. J.; Volokitin, A. I. (Eur. Phys. J. E, 2006)

(untitled) - Schallamach, A. (Wear, 1963)

(untitled) - Filippov, A. E.; Klafter, J.; Urbakh, M. (Phys. Rev. Lett., 2004)

(untitled) - Pogrebnjak, A. D.; Ponomarev, A. G.; Shpak, A. P.; Kunitskii, Yu. A. (Phys.-Usp., 2012)

(untitled) - Khomenko, A. V. (Phys. Lett. A, 2004)

(untitled) - Khomenko, A. V.; Lyashenko, Ya. A. (Phys.-Usp., 2012)